2023
DOI: 10.1109/tpel.2022.3216109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Sampling Parameters in FOCV-MPPT Circuits for Fast-Varying EH Sources

Abstract: The fractional open circuit voltage (FOCV) method is extensively used in low-power energy harvesting (EH) sources to extract maximum power. For fast-varying EH sources a fast sampling rate is required. This work theoretically analyzes the influence of the sampling time and period on the harvested power of sinusoidal EH sources. In addition, the circuit limitations to achieve a fast sampling rate are presented and circuits to deal with them proposed and implemented. Furthermore, one of the circuits is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In the long term, all the instants within a period To, where the The result in Equation ( 3) is achieved for the case of high sampling rates. In [16], it is shown that 99% of the maximum power is achieved for f s = 15f o . For any waveform type, Equation ( 3) is achieved whenever f s >> f omax , with f omax being the maximum frequency component of v ac .…”
Section: Rt Vt Vomentioning
confidence: 99%
See 3 more Smart Citations
“…In the long term, all the instants within a period To, where the The result in Equation ( 3) is achieved for the case of high sampling rates. In [16], it is shown that 99% of the maximum power is achieved for f s = 15f o . For any waveform type, Equation ( 3) is achieved whenever f s >> f omax , with f omax being the maximum frequency component of v ac .…”
Section: Rt Vt Vomentioning
confidence: 99%
“…In [16], experimental tests were carried out with a WEC embedded into a drifter and attached to a linear shaker (APS 129), with an excitation frequency of 2 Hz (f o ), in order to emulate the drifter's movement under a sea environment (Section V.C of [16]). A block schematic and a picture of the experimental setup are shown in Figures 4 and 5, respectively.…”
Section: Test With a Wecmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, [12], the Flyback converter is employed. There is no restriction on the converter to be used because a short circuit is never generated in the panel, or the panel is never disconnected from the converter (some algorithms need to perform these actions to obtain the MPP, for example, the fractional open circuit voltage (FOCV) and fractional short circuit current (FSCC) method) [18,19]. The disadvantage of the proposed scheme is that it will continuously oscillate even when the GMPP is reached (smaller oscillations will be generated).…”
Section: Introductionmentioning
confidence: 99%